2015
DOI: 10.17575/rpsicol.v29i2.1006
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity, Spirituality, and Mental Health in Portugal: A call for a conceptualisation, relationship, and guidelines for integration (a theoretical review)

Abstract: Abstract:In the Portuguese research society, particularly in the mental health field, little has been done regarding religiosity, spirituality and mental health. Thus, this paper strives to stimulate the interest in this area by providing an overview of the body of research on religiosity, spirituality and mental health, highlighting the role and importance these dimensions represent in the life of many people, whether in health or mental distress and illness. A brief review of the conceptualisation of religio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 88 publications
0
5
0
Order By: Relevance
“…Additionally, this is in agreement with the findings of Caldeira and colleagues (2016), who reported that the curricular units for inclusion of spirituality may include professional ethics. Freire and Moleiro (2015) and Janse van Rensburg (2014) highlighted the importance of ethical considerations to promote respect and non-discrimination, and should be part of collaboration with a religious adviser.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, this is in agreement with the findings of Caldeira and colleagues (2016), who reported that the curricular units for inclusion of spirituality may include professional ethics. Freire and Moleiro (2015) and Janse van Rensburg (2014) highlighted the importance of ethical considerations to promote respect and non-discrimination, and should be part of collaboration with a religious adviser.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors consider that the COVID-19 pandemic may be an ideal scenario to trigger spiritual-religious coping in society [ 29 ]. In Portugal, there is still a lack of mental health research regarding religiosity and spirituality [ 30 ]. Therefore, the objective of this study was to describe the role of spiritual-religious coping regarding fear and anxiety in relation to COVID-19 in healthcare workers in Portugal.…”
Section: Introductionmentioning
confidence: 99%
“…In the most recent Portuguese census in 2011, over 80% of the Portuguese population indicated that they were religious. The vast majority of these identified as Roman Catholic, but trends point to an increasing adoption of alternative religions and faiths (Freire & Moleiro, 2015). This significant expression of the Catholic church in Portugal was cemented due to affiliations with past political systems (Pinto & Rezola, 2007) and the internationally renowned events at Fátima (Dix, 2010).…”
Section: Conflict Between Religious/spiritual and Lgb Identitiesmentioning
confidence: 99%